Safety barriers in the chemical process industries: A state-of-the-art review on their classification, assessment, and management. (April 2022) - Yuan, Shuaiqi; Yang, Ming; Reniers, Genserik; Chen, Chao; Wu, Jiansong
Highlights: The paper provides a systematic review of research work on safety barriers in the chemical process industries. A novel classification of safety barriers, based on the identification and management of performance indicators, is proposed. Safety barrier functions are identified and illustrated using the resilience engineering concepts. The roadmap for future studies to develop integrated management of safety and security barriers for assurance of the resilience of chemical plants is suggested. Abstract: Barriers are used in various forms to assure the safety of chemical plants. A deep understanding of the literature related to safety barriers is essential to tackle the challenges in improving their design and management. This paper first provides an overview of the history of the development of the safety barrier concept. Subsequently, this paper elaborates a systematic review of the definition, classification, evaluation, performance assessment, and management of safety barriers in the chemical process industries. Based on the literature review, this study proposes a practical classification of safety barriers benefiting the identification of performance indicators and the collection of indicator-related data for safety barriers. The safety barrier functions are extended and illustrated by involving the resilience concept. Performance assessment criteria are proposed corresponding to the adaptability and recoverability of the safety barriers. Finally, the management of safety barriers is discussed. The roadmap for future studies to develop integrated management of safety and security barriers to ensure the resilience of chemical plants is suggested.